Changes in global vegetation activity and its driving factors during 1982–2013 - Zhao, Lin; Dai, Aiguo; Dong, Bo (Agricultural and forest meteorology, 2018)
•Globally, ENSO is the leading climatic driver of interannual variability of NDVIgs.•External anthropogenic forcing (mainly GHG) explains ∼66% of NDVIgs trend.•The rest of NDVIgs trend is attributable to internal climatic forcing (mainly AMO). Vegetation activity plays a crucial role in the global carbon cycle and climate. Many studies have examined recent changes in vegetation growth and the associated local climatic drivers. They revealed a global greening trend during the recent decades. However, few studies have analyzed how remote oceanic conditions affect land vegetation growth through atmospheric teleconnection, and the causes of the recent greening needs further investigation. In this study, we investigate the spatio-temporal variations (including trends) of vegetation activity using satellite data of growing-season normalized difference vegetation index (NDVIgs), and examine their relationship to local and remote climate oscillations and external anthropogenic forcing by statistical means. As expected, there is an increasing trend in global-mean NDVIgs from 1982–2013, with significant greening over Europe and many other land areas. NDVIgs is temperature-limited at northern high-latitudes, but water-limited in arid and semi-arid regions, and radiation-limited in the Amazon and eastern and southern Asia. Globally, El Niño-Southern Oscillation (ENSO) is the leading climatic driver of interannual variability of NDVIgs, especially over southern and eastern Africa, eastern Australia, northeastern Asia, and northern South America. Consistent with previous modeling studies, a regression-based attribution analysis suggests that historical anthropogenic forcing (mainly increases in greenhouse gases) explains about two thirds of the NDVIgs trend from 1982 to 2013, with the rest coming mainly from the Atlantic Multi-decadal Oscillation (AMO). Contributions to the recent NDVIgs trend from ENSO and Pacific decadal variability and Artctic Oscillation appear to be small.